Are They Coming Back? The Mobility of University Students in Switzerland after Graduation - Chantal Oggenfuss; Stefan C. Wolter (Institute of Labor Economics (IZA), 2018)
We analyze the internal mobility of university graduates in Switzerland. An empirically interesting question because not all the cantons have a university and therefore in some cantons students have to leave their home for studying but all the cantons have to bear the public costs for studying for their students irrespective of their study place. On average, approximately half of the students who had left their home canton in order to study, return to their home canton, and about half of those who do not return move onward from the canton where they studied to a third canton. Controlling for several factors explaining graduate mobility, we find that top performing students return less often than do low performers. As a consequence the home cantons, which cover the bulk of the costs also for the students that had left for studying in another canton, face a quantitative and qualitative disadvantage when losing mobile graduates.
Keywords: H52; H75; I23; J61; 330; student mobility; graduate mobility; brain gain; brain drain